Meteoroid Orbital Analysis: Connecting Meteorites and Asteroids - Shober, Patrick M. (Curtin University, 2021)
Since people started studying meteorites, scientists have attempted to better understand the parent bodies they originated from. Although, this is difficult because, unlike a terrestrial rock, you do not have access to the outcrop. The Near-Earth Object (NEO) population is the source of all meteorites found on Earth. Using the orbital data collected from the Desert Fireball Network, my work clarified the connections between meteorites and their source NEOs. I primarily did this analysis by employing rigorous numerical modeling techniques to constrain the dynamical and physical properties of asteroidal debris.